Integrating Linguistic Theories into English Language Education in Tourism Sectors: A Comprehensive Framework - Anggayana, I Wayan Agus (Akademi Komunitas MAPINDO, 2023)
The intersection of linguistic theories and English language education holds immense potential, especiallywhen applied to the context of the tourism sector. This article explores the development of a comprehensiveframework that seamlessly integrates linguistic theories into English language education, with a specific focuson the tourism industry. By combining the theoretical insights of linguistics with practical language teachingstrategies, educators and stakeholders in the tourism sector can enhance communication skills and culturalcompetency among professionals. The article presents a holistic approach that aims to bridge the gap betweenlinguistic theories and language education, offering a roadmap for effective integration in the tourism domain.This research is descriptive qualitative research. 10 Competence units, 24 elements of competence and 20materials were found in this research.Keywords: Linguistic, English, Education, Framework